Pembangunan Sistem Informasi Manajemen UMKM pada Plantshopedia - Mohammad Annur Ramadhan; I Putu Deny Arthawan Sugih Prabowo; Sri Rahayu Natasia (Ikatan Ahli Informatika Indonesia, 2021)
Information Systems/Information Technology (IS/IT) is growing rapidly and the benefits are very broad, especially in the business sector. Plantshopedia as one of the micro, small and medium enterprises (MSMEs) has 4 (four) core business processes that able to be supported by the use of IS/IT will have a major impact on the achievement of its business goals. However, currently, Plantshopedia does not have IS/IT capable of supporting its business processes, especially in product inventory management. Therefore, a product inventory management information system was developed using the Scrum method by going through several stages, including: project initiation, sprint planning, daily scrum, sprint review, and sprint retrospective. The results obtained are that a system has been developed, namely Management Information Systems of Plantshopedia (MISoP) which is the result of implementing a product backlog consisting of 32 backlog items with a total of 4 (four) sprint rounds in system development for 4 (four) months. In addition, an assessment of the level of satisfaction with the use of MISoP has also been made through a questionnaire with respondents from internal Plantshopedia. The results obtained from the questionnaire are 3 respondents from Plantshopedia internal who have agreed that the MISoP system is easy to operate and able to assist in solving problems experienced by Plantshopedia so that they are satisfied with the benefits of the system.